Photoelectrochemical CO2 Reduction Products Over Sandwiched Hybrid Ga2O3:ZnO/Indium/ZnO Nanorods - Jang, Hye Ji; Yang, Ju Hyun; Maeng, Ju Young; Joo, Min Hee; Kim, Young Jun; Rhee, Choong Kyun; Sohn, Youngku (Frontiers in Chemistry, 2022)
Recycled valuable energy production by the electrochemical CO2 reduction method has explosively researched using countless amounts of developed electrocatalysts. Herein, we have developed hybrid sandwiched Ga2O3:ZnO/indium/ZnO nanorods (GZO/In/ZnONR) and tested their photoelectrocatalytic CO2 reduction performances. Gas chromatography and nuclear magnetic spectroscopy were employed to examine gas and liquid CO2 reduction products, respectively. Major products were observed to be CO, H2, and formate whose Faradaic efficiencies were highly dependent on the relative amounts of overlayer GZO and In spacer, as well as applied potential and light irradiation. Overall, the present study provides a new strategy of controlling CO2 reduction products by developing sandwiched hybrid catalyst system for energy and environment.